Methotrexate Therapy for Ectopic Pregnancies: A Tertiary Center Experience - Ozyuncu, Ozgur; Tanacan, Atakan; Duru, Sinem Ayse; Beksac, Mehmet Sinan (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective Our aim is to demonstrate the importance of methotrexate (MTX) therapy for the treatment of ectopic pregnancy (EP).Methods This retrospective study consisted of 99 patients (72 tubal EPs, 20 pregnancies of unknown location (PUL), 4 cesarean section (CS) scar EPs and 3 cervical EPs) treated with MTX.Results Methotrexate therapy was successful in 68.5% of EPs. There were statistically significant differences between the MTX success and failure groups based on ultrasonographic findings, patient complaints, gestational week and serum human chorionic gonadotropin (hCG) values. The MTX success rates in PUL and tubal pregnancies were 95% and 61.1%, respectively. The MTX success rates in single-dose, two-dose and multi-dose protocol groups were 86.9%, 28.6% and 40%, respectively. All cervical and CS scar ectopic pregnancies were treated successfully with MTX therapy.Conclusion Methotrexate might be the first-line treatment option for EPs under certain conditions. Physicians must be more cautious in cases with higher hCG values, the presence of abdominal-pelvic pain, the presence of fetal cardiac activity, larger gestational sac (GS) diameters, and more advanced gestational weeks according to the last menstrual period.
Keywords: methotrexate; ectopic pregnancy; medical gynecology; diagnosis